Electronic structure-sunlight driven water splitting activity correlation of (Zn1-yGay)(O1-zNz) - Rajaambal, Sivaraman; Yadav, A. K.; Jha, Shambhu Nath; Bhattacharyya, Dibyendu; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2014)
(Zn1-yGay)(O1-zNz) (y <= 0.10; z <= 0.15) solid solutions have been investigated for their electronic structure and visible light photocatalytic activity, and a correlation was found between them. (Zn1-yGay)(O1-zNz) with ZnO as the major component have been synthesized by a solution combustion method in 10 minutes using simple raw materials. The local structures of Zn K edge and Ga K edge, and changes in the chemical environment with the incorporation of Ga and N in ZnO were determined by EXAFS study. EXAFS and XRD results suggested the dissolution of GaN in the ZnO lattice. The homogeneity of the solid solution was demonstrated from HRTEM studies. Photoluminescence studies revealed the creation of a new band at the top of the ZnO valence band (VB), and thus the broadening of the VB of (Zn1-yGay)(O1-zNz) or a decrease in the band gap was attributed to the origin of visible light absorption. UV-Vis spectral studies showed light absorption up to 550 nm, which directly supports the VB broadening. Predominant oxygen vacancies and high photocorrosion observed for ZnO were fully suppressed for (Zn1-yGay)(O1-zNz) , indicating the minimization of defects, and thus more sustainability under irradiation conditions. The bare solid solution exhibited reasonable and promising activity for solar hydrogen evolution and photoelectrochemical current generation at 0 V. The present work explained factors such as the preparation method, single phase structure with the stabilization of integral parts, homogeneity in the structure, compensation of oxygen vacancies, and suppression of the density of recombination centres that play a pivotal role in realizing solar energy harvesting.

Investigations into variations in local cationic environment in layered oxide series InGaO3(ZnO)(m) (m=1-4) - Narendranath, Soumya B.; Yadav, Ashok Kumar; Ajithkumar, Thalasseril G.; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Dey, Krishna K.; Raja, Thirumalaiswamy; Devi, R. Nandini (Dalton Transactions, 2014)
Layered oxides of the series InGaO3(ZnO)(m) (m = 1-4) are interesting due to their structural anisotropy. Here, we report a comprehensive study of their structural details, focusing on the local cationic environment in bulk powder samples by MASNMR and EXAFS, which is hitherto not attempted. It is found that the Ga geometry varies gradually from pure pentacoordinated to a mixture of penta and tetracoordinated with increasing amounts of tetracoordination as we move across the series, contrary to previous reports suggesting exclusively trigonal bipyramidal coordination in all the compounds. A similar observation is also made in the case of Zn and structural evolution involving the dissolution of Ga in a ZnO4 tetrahedral network in a sandwich layer can be discerned, as the insulating ZnO layer size increases.

Photocatalytic H-2 evolution from water-methanol system by anisotropic InFeO3(ZnO)(m) oxides without cocatalyst in visible light - Narendranath, Soumya B.; Yadav, Ashok Kumar; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2014)
InFeO3(ZnO)(m), series of oxides are found to give unprecedented H-2 evolution from water-methanol mixtures without using any cocatalysts. This family of compounds has an anisotropically layered structure in which Zn/FeOn polyhedra are sandwiched between InO6 octahedral layers. Local structure characterization by X-ray absorption spectroscopy reveals that Zn coordination changes from pentacoordinated to tetrahedral geometry across the series, whereas Fe geometry remains trigonal bipyramidal in all the compounds. This peculiar structure is conducive for a spatial separation of photogenerated charges reducing recombination losses. Band gap energies calculated from absorption spectra indicate potential visible light activity, and this may be due to the orbital mixing of Fe 3d and O 2p as revealed by pre-edge features of X-ray absorption spectra. Band positions are also advantageously placed for a visible light H-2 generation and is indeed found to be the case in methanol-assisted water splitting with standardized hydrogen evolution of similar to 19.5 mmol g(-1) h(-1) for all the catalysts.
Keywords: anisotropic structure; H-2 evolution; InFeO3(ZnO)(m); layered oxide; photocatalytic water splitting

Nitrogen doping in oxygen-deficient Ca2Fe2O5: a strategy for efficient oxygen reduction oxide catalysts - Jijil, Chamundi P.; Lokanathan, Moorthi; Chithiravel, Sundaresan; Nayak, Chandrani; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Babu, P. D.; Kakade, Bhalchandra A.; Devi, R. Nandini (ACS Applied Materials and Interfaces, 2016)

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts